Status of duckweed genomics and transcriptomics. (4th July 2014) - Wang, W.; Messing, J.
Abstract: Duckweeds belong to the smallest flowering plants that undergo fast vegetative growth in an aquatic environment. They are commonly used in wastewater treatment and animal feed. Whereas duckweeds have been studied at the biochemical level, their reduced morphology and wide environmental adaption had not been subjected to molecular analysis until recently. Here, we review the progress that has been made in using a DNA barcode system and the sequences of chloroplast and mitochondrial genomes to identify duckweed species at the species or population level. We also review analysis of the nuclear genome sequence of Spirodela that provides new insights into fundamental biological questions. Indeed, reduced gene families and missing genes are consistent with its compact morphogenesis, aquatic floating and suppression of juvenile‐to‐adult transition. Furthermore, deep RNA sequencing of Spirodela at the onset of dormancy and Landoltia in exposure of nutrient deficiency illustrate the molecular network for environmental adaption and stress response, constituting major progress towards a post‐genome sequencing phase, where further functional genomic details can be explored. Rapid advances in sequencing technologies could continue to promote a proliferation of genome sequences for additional ecotypes as well as for other duckweed species.